2008
DOI: 10.1134/s1063785008040081
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the near-surface layers of a copper foil under the action of a volume gas discharge in air at atmospheric pressure

Abstract: -We have studied the modification of the near-surface layers of a copper foil under the action of a volume gas discharge, which was generated in air at atmospheric pressure by nanosecond highvoltage pulses of both negative and positive polarity applied between the foil and an electrode with a small radius of curvature. It is established that the surface layer of the discharge-treated copper foil in the central region is cleaned from carbon contaminations, while oxygen atoms penetrate in depth of the foil. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Studies of nano-hardness of the treated samples have shown that the hardness of niobium surface layers decreased with increasing of exposure dose (see Fig. 4), that is the opposite of results for copper and steel obtained in the early experiments in which the hardness increased [7,9]. Obviously, it concerned with the fact that niobium oxides are more porous in comparison with the pure niobium.…”
Section: Depth Nmmentioning
confidence: 68%
“…Studies of nano-hardness of the treated samples have shown that the hardness of niobium surface layers decreased with increasing of exposure dose (see Fig. 4), that is the opposite of results for copper and steel obtained in the early experiments in which the hardness increased [7,9]. Obviously, it concerned with the fact that niobium oxides are more porous in comparison with the pure niobium.…”
Section: Depth Nmmentioning
confidence: 68%
“…A runaway electrons preionized diffuse discharge was used for pumping different gas lasers [6], for creation VUV and UV excilamps [14][15][16], and for modification and cleaning of metal surfaces [17]. We suppose that REP DD will have widespread use in different fields.…”
Section: Discussionmentioning
confidence: 99%
“…The REP DD plasma can be used as sources of VUV spontaneous radiation 15,16 , for cleaning and modification of metal surface 22 . Diffuse discharges are started to apply for excitation of gas lasers [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…During recent ten years intensive study of run-away electron preionized volume (diffuse) discharge (REP DD) has been renewed [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and REP DD was found to have a number of unique properties. Specifically, it was shown that the specific input electric power can be as high as ~800 MW per cubic cm 9,10 .…”
Section: Introductionmentioning
confidence: 99%